Fire in the Wildland-Urban Interface: Selecting Firewise Shrubs to Reduce Wildfire Risk - Annie Hermansen-Báez; Raelene Crandall; Wayne Zipperer; Alan Long; Annie Behm; Dawn McKinstry; Anne Andreu (EDIS)
Properties in the wildland-urban interface frequently use shrubs in landscaping. Although shrubs are attractive, some types can be risky to plant near structures in fire-prone areas. Property owners in such areas should consult existing guides for shrubs that do not burn easily and should routinely maintain shrubs and other vegetation within the defensible space around houses and other structures.